Court expert status in poland - flagging up selected problems - Skubisz-Ślusarczyk, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The intent of this written presentation is to analyse the multi-faceted issue of the position and functioning of court experts in the Polish legal system. Particular attention should be paid in this respect to the appointment and verification of the competencies of candidates for experts, as well as to the instruments of control over their work. These selected aspects are extremely important, not only from the point of view of public interest, but in particular from the perspective of the party’s right to a fair trial, and to have the case heard within a reasonable time. The problems identified and briefly discussed have a structural and systemic nature, and result in arrangements which confirm the necessity for legislative changes proposed for many years, relating to court experts as well as to the practice of judicial authorities. The discussion of these issues has an informative purpose, especially for readers unfamiliar with the Polish legal system.
Keywords: court expert; expert status; false opinion; unreliable opinion; late opinion; expert’s liability